Integrating Oncology and Palliative Home Care in Italy: The Experience of the "L'Aquila per la Vita" Home Care Unit. Issue 2 (March 2013) - Porzio, Giampiero; Aielli, Federica; Verna, Lucilla; Martella, Francesco; Aloisi, Paolo; Ficorella, Corrado
Aim: To evaluate the efficacy of a home care program, closely integrated with a medical oncology department. Patients and methods: The charts, prospectively recorded, of all the patients treated at home by the "L'Aquila per la Vita" Home Care Unit from August 2006 to December 2011, were reviewed. The number of patients, home accesses, length of the home care, hospital admission, emergency calls, and the place of death were recorded. Data were analyzed considering the origin of the patients (medical oncology department or other). Results: A total of 461 patients was followed at home for a total of 10, 503 home accesses (median accesses/patient, 20; range, 1–159). The median length of home care was 76 days (range, 2–643 days). The median was 101 days for patients coming from the medical oncology department and 53 days for patients coming from other origins ( P <0.0005). There were 428 emergency calls (4.1% of all the home accesses). Emergency calls accounted for 253 of 7, 364 home accesses (3.4%) among patients coming from the medical oncology department and for 175 of 3, 139 home accesses (5.6%) among patients coming from other origins ( P = 0.00005). Eighty of 461 patients (17.3%) required one in-hospital admission and 19/461 patients (4.1%) more than one. Fifty-nine of 259 (17.8%) patients coming from the medical oncology department and 40 of 186 (26.9%) coming from other origins required in-hospital admissions ( P = 0.04). A total of 311 patients died (163 coming from the medical oncology department and 148 from other origins). Twenty-eight of 163 (17.1%) coming from the medical oncology department and 52 of 148 (35.1%) coming from other origins died in the hospital ( P = 0.0002). Conclusions: A multidisciplinary and expert team, closely integrated with the hospital, can guarantee a long length of home care, avoiding hospitalization and closing the gap between the patients' preferences and the services offered regarding the place of death.